2013
DOI: 10.1097/igc.0b013e31828189b2
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and Ovarian Cancer Risk: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: This study suggests that women with diabetes have a moderately increased risk of ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 47 publications
3
50
0
1
Order By: Relevance
“…Several in vitro and in vivo pre-clinical investigations have detected a growth-static effect of metformin also in gynecological malignancies, including ovarian cancer (40,(48)(49)(50)(51)(52)(53)(54)(55), endometrial cancer (23-25, 55, 59-65, 67, 72, 74, 89) and breast cancer (12,17,22,38,130,131,134,135), mainly due to the effects of drug on the IGF system and different intracellular signaling transduction pathways .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several in vitro and in vivo pre-clinical investigations have detected a growth-static effect of metformin also in gynecological malignancies, including ovarian cancer (40,(48)(49)(50)(51)(52)(53)(54)(55), endometrial cancer (23-25, 55, 59-65, 67, 72, 74, 89) and breast cancer (12,17,22,38,130,131,134,135), mainly due to the effects of drug on the IGF system and different intracellular signaling transduction pathways .…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis showed that patients with diabetes exhibit an increased risk of ovarian cancer (53). Moreover, diabetic women are more likely to have poorly differentiated tumor and to experience poor clinical outcome when compared with non-diabetic women, which could be due to the growth-promoting effect of elevated serum levels of insulin and IGF-1 (54,55).…”
Section: Clinical Datamentioning
confidence: 99%
“…Type 2 diabetes is positively associated with cancers of the colon, breast (postmenopausal) and pancreas. Patients with type 2 diabetes are at increased risk of cancers of the liver, pancreas, endometrium, colorectum, breast, and bladder [70][71][72]. Current estimates show an overall hazard ratio (HR) of 1.23 for breast cancer incidence, and 1.26 for colorectal cancer incidence in patients with diabetes compared to those without diabetes [73].…”
Section: Avoiding Weight-related Co-morbidities (Diabetes and Heart Dmentioning
confidence: 94%
“…Data obtained from meta-analyses of diabetes and cancer risk. Data from [7][8][9][10][11][12][13][14][15][16]. CI, confidence interval; RR, relative risk.…”
Section: Insulin and Insulin-like Growth Factorsmentioning
confidence: 99%
“…Many meta-analyses have been performed examining the association between diabetes and the risk of cancer at specific sites. Diabetes is associated with an increased risk of hepatocellular, pancreatic, renal, gastric, colorectal, endometrial, ovarian, bladder and breast cancer as well as non-Hodgkin lymphoma, T cell lymphoma and leukemia (Table 3) [8][9][10][11][12][13][14][15][16]. Although certain cancers are known to have specific risk factors, such as smoking for lung cancer and chronic infectious hepatitis in hepatocellular cancer, diabetes has been associated with an increase in these cancers in certain populations.…”
Section: Introductionmentioning
confidence: 96%